Managing acute severe ulcerative colitis in the hosptialised setting. Issue 4 (8th July 2014) - McClements, David; Probert, Chris
Abstract : Ulcerative colitis affects approximately 146 000 people in the UK and is the most common form of inflammatory bowel disease. The majority of patients will have uncomplicated disease, but around 1 in 10 patients will develop acute severe colitis. Despite modern medical management, colectomy rates of 27% and mortality rates of 1% are still reported. Good supportive care and intravenous corticosteroids remain the mainstay of treatment, but up to one-third of patents will not respond. The Travis criteria allow early recognition of those patients failing to improve by day 3, allowing timely planning of medical rescue therapy or surgery. Rescue therapy with either infliximab or ciclosporin appears equally efficacious. Patients naive to thiopurines seem to have better colectomy-free survival rates following rescue therapy than those previously exposed. We review the published evidence behind the conventional management of acute severe ulcerative colitis.